Answer:
-10x + 38
Step-by-step explanation:
-2(x-3) + 4(-2x+8) -------> -2x + 6 - 8x + 32 ----------> -10x + 38
Answer:
He's correct.
Step-by-step explanation:
As long as there is no change in sign of the variables.
Answer: x>-6
Explanation: -2x -6>-18
-2x >-12
-x>6
X>-6
To solve for r, you would start by subtracting p from both sides.
2m - p = -q/r
Multiply everything by r.
2mr - pr = -q
Factor r out of the left side of the equation.
r(2m - p) = -q
Divide both sides by (2m - p).
r =
.
This would be 525 / 0.70 = $750 Answer